Upaya Pustakawan Dalam Meningkatkan Keterpakaian Koleksi Braille Di Dinas Perpustakaan Dan Arsip Provinsi Sumatera Utara - Nur Syahadah Sinaga; Nurhayani Nurhayani; Nabila Yasmin (Lembaga Pengembangan Kinerja Dosen, 2024)
The purpose to be achieved from this study is to find out how efforts are made by librarians to improve the wearability of braille collections in the Library and Archives Office of North Sumatra Province. This research uses descriptive analysis method using qualitative approach. With data collection techniques, namely observation, interviews and documentation. The informant in this study focused on librarians who served as managers of braille collections at the Library and Archives Office of North Sumatra province. The results of this study obtained information that librarians of the North Sumatra Provincial Library and Archives Office have efforts to increase braille collections, namely: 1.) Promoting braille collections, 2.) Cooperation between libraries and disability organizations, 3.) Conducting counseling, 4.) Development and preservation of braille collections. Librarians' efforts in improving the wearability of braille collections are carried out so that braille collections can be put to good use by blind people.